Pelaksanaan Metode Ceramah Dan Tanya Jawab Pada Mata Pelajaran Fikih - Azizah, Wafiq (EL-EMIR Institute, 2025)
This study aims to describe the implementation of lecture and question-and-answer methods in Fiqh learning, analyze their advantages and disadvantages, and identify supporting and inhibiting factors in their application. This research uses a qualitative descriptive approach with data collection techniques including interviews, observations, and documentation. Informants consist of Fiqh teachers and students at MAS Hidayah. The results show that the lecture method is effective in delivering material systematically and comprehensively, while the question-and-answer method enhances interaction, participation, and students’ critical thinking skills. The combination of these methods creates a more interactive, reflective, and analytical learning environment. Supporting factors include teacher competence, student motivation, and a conducive classroom environment, whereas inhibiting factors include time constraints, students’ hesitation to ask questions, and classroom distractions. In conclusion, integrating lecture and question-and-answer methods can improve the quality of Fiqh learning and support the holistic development of students’ character and potential.